The Influence of Peer Editing Technique on Students’ Essay Writing Skill - ., Subadiyono (KnE Social Sciences, 2018)
This study aimed to describe the influence of the peer editing technique on students’ essay writing in the Study program of Indonesian Language and Literature Education, Faculty of Teacher Training and Educational Science, Universitas Sriwijaya. Data were collected from 21 students of Indonesian and literature education. The results showed that the post-test mean score was higher than the pretest. In addition, the t-statistic was higher than the t-table: 8.638 > 1.724. This shows that the peer editing technique influenced students’ essay writing. By using peer editing, five important aspects (format, mechanic, organization, and grammar) were emphasized in essay writing. Keywords: essay writing, peer editing, education